2017
DOI: 10.1037/amp0000104
|View full text |Cite
|
Sign up to set email alerts
|

Close social ties and health in later life: Strengths and vulnerabilities.

Abstract: The world is aging at an unprecedented rate, with older adults representing the fastest growing segment of the population in most economically developed and developing countries. This demographic shift leaves much uncharted territory for researchers who study social relationships and health. Social relationships exert powerful influences on physical health in later adulthood, a critical consideration given age-related increases in the prevalence of chronic health conditions and physical disability. A large bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 97 publications
4
103
0
1
Order By: Relevance
“…That is, older people tend to increasingly prefer to regulate themselves through internal changes rather than acting upon others or the environment (Heckhausen & Schulz, 1995). Consistent with this line of thinking, research has shown that older workers preferentially engage in problem-focused active coping (Hertel, Rauschenbach, Thielgen, & Krumm, 2015) and tend to respond to conflict with less outward responses (Diehl et al, 1996;Rook & Charles, 2017). Where younger adults may feel compelled to externalize their reactions to self-esteem threat-in ways that may be detrimental to service delivery-older adults may opt to manage reactions internally, preserving performance in the process.…”
Section: Integrating the Strengths And Vulnerabilities Of Agingmentioning
confidence: 87%
See 1 more Smart Citation
“…That is, older people tend to increasingly prefer to regulate themselves through internal changes rather than acting upon others or the environment (Heckhausen & Schulz, 1995). Consistent with this line of thinking, research has shown that older workers preferentially engage in problem-focused active coping (Hertel, Rauschenbach, Thielgen, & Krumm, 2015) and tend to respond to conflict with less outward responses (Diehl et al, 1996;Rook & Charles, 2017). Where younger adults may feel compelled to externalize their reactions to self-esteem threat-in ways that may be detrimental to service delivery-older adults may opt to manage reactions internally, preserving performance in the process.…”
Section: Integrating the Strengths And Vulnerabilities Of Agingmentioning
confidence: 87%
“…As people age, they report feeling more hurt by social rejection (Cheng & Grühn, 2015) yet, nevertheless, respond less negatively to social rejection (Charles & Carstensen, 2008) and unpleasant social interactions (Luong & Charles, 2014). Generally, as people grow older, their emotion regulation performance tends to improve (Doerwald et al, 2016; see also Blanchard-Fields, 2007), and they are less likely to externalize and lash out at interpersonal conflict (Diehl, Coyle, & Labouvie-Vief, 1996;Rook & Charles, 2017). At the same time, people experience more distress as they age when their social needs are not met (Ong, Rothstein, & Uchino, 2012), and their physiological recovery from stress also becomes impaired as biological aging sets in (Wrzus, Müller, Wagner, Lindenberger, & Riediger, 2014).…”
Section: Integrating the Strengths And Vulnerabilities Of Agingmentioning
confidence: 99%
“…Scholars have indicated, however, that systemic changes to address health disparities cannot be achieved without the collaboration of multiple partners and systems (Kazak et al, 2010), the political will to change the national discourse (Crowley, Supplee, Scott, & Brooks-Gunn, 2019), and the commitment to engage in intersectoral antipoverty, health, and economic justice initiatives (Bullock, 2019). Although previous public health, education, and justice systems literature has addressed the importance of addressing social determinants of health to improve the quality of life and well-being of diverse communities across the life span (Chen, Brody, & Miller, 2017;Pietromonaco & Collins, 2017;Rook & Charles, 2017), additional literature in the field of psychology is needed on the urgent need for systemic change to improve the psychological health outcomes of individuals living in underprivileged conditions (Solar & Irwin, 2010). In line with the World Health Organization's (2011) conceptual framework for action on the social determinants of health (SDH), the authors use the terms marginalized, disadvantaged, and underprivileged to refer to individuals who due to their lower position in the U.S.'s social hierarchy, experience higher exposure and vulnerability to health-compromising conditions such as COVID-19.…”
Section: Covid-19mentioning
confidence: 99%
“…In addition, older adults prioritize emotion‐regulation goals (Carstensen et al, ), partly because––as discussed earlier––negative emotions that are elicited through negative social interactions detract from older people's well‐being and health (Rook & Charles, ). This development might render social avoidance goals in peripheral social relationships more beneficial as people age.…”
Section: Social Development Across Adulthoodmentioning
confidence: 99%